Pemanfaatan Pemasaran Digital, Sertifikasi Halal dan Diversifikasi Produk Meningkatkan Pendapatan Kelompok Pengolahan Makanan Beku: Utilization of Digital Marketing, Halal Certification, and Product Diversification to Increase Income of Frozen Food Processing Groups - Maulida, Sri; Humaidi, Humaidi; Rizqiana, Sista; Tio, Yuansen; Rahmawati, Riska Maulidia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service program aims to increase the income of the Frozen Food Processing Group, Poklahsar Paiwakan Banua Haruyan (PBH), in Haruyan Seberang Village, which faces challenges in developing digital marketing, halal certification, and product diversification. The goal of this program is to enhance the partners' income by applying technology and innovation in producing seasoned steamed chicken and duck (ungkep) as a diversification from fish-based products. The methods used include socialization, training, technology implementation, and assistance with halal certification. The activities began with socialization and training on August 31, 2024, followed by technology and production training on September 11 and 29, 2024. The results show a 55% increase in participants' knowledge after the training, with a *paired t-test* indicating a significance value of 0.000, demonstrating the program's success in enhancing participants' understanding. Income increased by 100% from both online and offline sales, while production grew by 18%. Additionally, halal certification assistance was conducted from September 22 to 25, 2024. With the implementation of digital marketing, new technology, and product diversification, Poklahsar Banua Haruyan is now ready to market halal products digitally, which is expected to improve its competitiveness and revenue. This program is designed to be sustainable with continuous assistance until Poklahsar Banua Haruyan becomes independent. The focus is on ensuring consistent production and marketing, adapting to market trends, and utilizing exhibitions organized by the HST government. The team also supports the development of a long-term business plan to maintain business stability, expand market reach, and drive sustainable growth.